ANALYSIS OF RISKS ARISING FROM THE USE OF DIGITAL PLATFORMS (Web of Teachers: Inderscience Research, 2025)
In the context of the global information economy, the rapid development of the digital economy is mainly observed in countries that have fully transitioned to a market economy. In contrast, in countries still operating under traditional contractual systems, digital economic growth is relatively slow. Measuring the value of the digital economy presents challenges for national economies and companies due to the lack of a universally accepted definition and precise measurement mechanisms. This article examines various risks associated with digital platforms, including fraud, misinformation, cybercrimes, and manipulative algorithms. Additionally, the study analyzes financial fraud, personal data theft, and the social and psychological consequences of digital platforms. Based on international experiences, recommendations for developing Uzbekistan’s digital economy and ensuring cybersecurity are provided.